Th17 cells in systemic lupus erythematosus share functional features with Th17 cells from normal bone marrow and peripheral tissues - Henriques, A (2011)
This study was designed to investigate the functional heterogeneity of human Th17 and how their plasticity shapes the nature of immune cell responses to inflammation and autoimmune diseases, such as systemic lupus erythematosus (SLE). We evaluated functional Th17 cell subsets based on the profile of cytokine production in peripheral blood (PB), bone marrow aspirates (BM) and lymph node biopsies (LN) from healthy individuals (n = 35) and PB from SLE patients (n = 34). Data were analysed by an automated method for merging and calculation of flow cytometric data, allowing us to identify eight Th17 subpopulations. Normal BM presented lower frequencies of Th17 (p = 0.006 and p = 0.05) and lower amount of IL-17 per cell (p = 0.03 and p = 0.02), compared to normal PB and LN biopsies. In the latter tissues were found increased proportions of Th17 producing TNF-α or TNF-α/IL-2 or IFN-γ/TNF-α/IL-2, while in BM, Th17 producing other cytokines than IL-17 was clearly decreased. In SLE patients, the frequency of Th17 was higher than in control, but the levels of IL-17 per cell were significantly reduced (p < 0.05). Among the eight generated subpopulations, despite the great functional heterogeneity of Th17 in SLE, a significant low proportion of Th17 producing TNF-α was found in inactive SLE, while active SLE showed a high proportion producing only IL-17. Our findings support the idea that the functional heterogeneity of Th17 cells could depend on the cytokine microenvironment, which is distinct in normal BM as well as in active SLE, probably due to a Th1/Th2 imbalance previously reported by our group.